PENGARUH KEGIATAN MELUKIS INKONVENSIONAL TEKNIK TUTUP TERHADAP KREATIVITAS ANAK USIA 5-6 TAHUN - Putri Clawson; Siti Jubaida (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2018)
The purpose of this study was to find out how much influence the unconventional closing technique of painting activities on the creativity of children aged 5-6 years at the Akramunnas Islamic Kindergarten in Pekanbaru. This research uses a quantitative approach and the type of research is experimental. Experimental research is research that provides treatment of research variables (independent variables), then observes the consequences of these treatments on research objects (dependent variables). The sample in this study were all early childhood in the Akramunnas Islamic Kindergarten in Pekanbaru, which were 2 classes, B1 class as many as 20 children as an experimental class and B2 as many as 20 children as a control class. Based on the results of data analysis and discussion in this study, it can be concluded that there is an influence of the unconventional closing technique of painting activities on the creativity of children aged 5-6 years at the Islamic National Academy in Pekanbaru. This can be seen from the difference in the value of experiments and controls. Unconventional closing technique painting activities have an effect of 25.4%. Based on the t test shows that the search results t arithmetic greater than t table that is 1,729 <15,714. This means that drawing screen printing has a positive influence on the creativity of children aged 5-6 years at the Pekanbaru Akramunnas Islamic Kindergarten.